Two forgotten processes: the demographic catastrophe and the imposition of «reductions of Indians» in northern Peru - Figueroa Luna, Guillermo (2020)
It is verified that the apology for the foundation of cities for minorities, as the supposed beginning of civilization at the beginning of the Colony (16th century), added to the silence on the forced imposition of “Indian” towns or reductions, conceal the terrible demographic catastrophe in the North Peruvian Coast, caused by the acute exploitation and oppression of the majority native population, next to the new diseases and the impoverishment of the diet of the “Indians”.